2015
DOI: 10.5152/dir.2015.15003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of second-opinion radiology consultations to reassess the cervical spine CT scans: a study on trauma patients referred to a tertiary-care hospital

Abstract: M agnetic resonance imaging (MRI) is a widely used diagnostic tool for breast imaging in daily practice, with its high sensitivity to detect primary, recurrent, and residual breast cancer. Breast MRI serves as a reliable problem-solving tool in case of inconclusive mammography and ultrasonography (US) findings. It can be used to monitor the results of neoadjuvant chemotherapy and it may also contribute to preoperative evaluation of known lesions. With increasing use of MRI, number of breast lesions visible onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Second opinions are described in the literature as an important tool for preventing medical errors and for providing patients with the most effective treatment possible. 15 Therefore, both physicians and patients may benefit from second opinion consultations. However, this study demonstrated that acute care patients often show passive attitude towards seeking a second opinion during hospitalization, although some reported seeking a second opinion in the past (not during a hospitalization period).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second opinions are described in the literature as an important tool for preventing medical errors and for providing patients with the most effective treatment possible. 15 Therefore, both physicians and patients may benefit from second opinion consultations. However, this study demonstrated that acute care patients often show passive attitude towards seeking a second opinion during hospitalization, although some reported seeking a second opinion in the past (not during a hospitalization period).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that examined second opinions during hospitalization focused on second opinions initiated by physicians. [14][15] Studies that did examine patients' initiated second opinion were mostly among oncology patients. 9 These studies focused on reasons, motives and expectations in relation to second opinion, 1,16 and did not focus on the barriers patients are facing when seeking a second opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Having said that it is known that a second or more opinions on medical images increases the accuracy of the diagnosis for various diseases (e.g., in neuroradiology [4], for breast cancer diagnosis [5] or for reassessment of cervical spine CTs [6]), the disparity between the number of professionals and the amount of data has become a major challenge with respect to accurate and efficient reporting. Due to the sheer number of images and the lack of adequate tools, the time for reviewing radiological images has become less-not just for diagnostic reporting, but also for surgical preparation, for example.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…[2] Thus, it has become important for the patient's treatment plan to immediately reconfi rm the CT image of a transferred patient in the referred ED. [3] However, previous studies conducted on patients visiting EDs reported significant discrepancies of interpretations between EDs for the same CT image. [2][3][4][5] If such a discrepancy is found in the ED, the clinical process could change, and the performance of additional imaging may be required, resulting in unnecessary radiation exposure and an increased cost burden on patients.…”
mentioning
confidence: 98%
“…[3] However, previous studies conducted on patients visiting EDs reported significant discrepancies of interpretations between EDs for the same CT image. [2][3][4][5] If such a discrepancy is found in the ED, the clinical process could change, and the performance of additional imaging may be required, resulting in unnecessary radiation exposure and an increased cost burden on patients. [6] Moreover, additional imaging studies may lead to prolonged ED length of stay (LOS), in turn causing ED crowding, which can adversely affect the patient's clinical results and reduce the patient's satisfaction level.…”
mentioning
confidence: 98%